In-hospital mortality risk factors in patients with ascites due to cirrhosis - Vicco,Miguel Hernan (2015)
Introduction: ascites is one of the most common complications of cirrhosis associated with a high rate of mortality. Although several scores have been developed in order to assess the prognosis of the disease, they were designed for predicting liver transplantation requirements and mortality in the short term, but not while in hospital. The aim of this study was to weigh risk factors for in-hospital mortality in adult patients with ascites due to alcoholic cirrhosis. Material and methods: we performed a cross-sectional study in 180 adult patients with diagnosis of cirrhosis with portal hypertension associated with high alcohol intake. The diagnosis of cirrhosis was made by liver echography and portal hypertension was defined by clinical features plus serum-ascites albumin gradient. Sampled individuals were subjected to complete clinical examination. Child Pugh and the MELD scores were applied in all the patients. Results: nineteen patients died while in-hospital. Mortality was associated with increased levels of serum white blood cell, urea, creatinine, prolonged prothrombin time, aspartate aminotransferase and alanine aminotransferase. We conducted a multiple binary logistic to predict in-hospital mortality which yielded that serum urea, creatinine and prothrombin time made a significant contribution to prediction with an OR 14 (95% CI 12.8 - 16.7 p = 0.03), 2 (95% CI 0.5 - 3.47, p = 0.04), and 2 (95% CI 1.03 - 2.31, p = 0.01) linearly-related. Conclusions: our results suggest that acute renal failure and prolonged prothrombin time are predictors of in-hospital mortality in patients with portal hypertension due to alcoholic cirrhosis.